The battles of Monte Cassino : the campaign and its controversies - Harper, Glyn, 1958- (Allen & Unwin, 2013)
The first thematic analysis of the Battles of Monte Cassino brings to light new and controversial ideas and information about some of the most critical battles of the Second World War.